Dampak Ekonomi Pengembangan Daya Tarik Wisata “Hot Spring” Di Kecamatan Marobo, Kabupaten Bobonaro, Timor-Leste - Pieda, Gracita Chiana do Rêgo Cornélio da; Anom, I Putu (JURNAL DESTINASI PARIWISATA; Vol 7 No 2 (2019): VOL 7, NO 2 (2019): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i02.p03, 2019)
The economic impact of development of Marobo District’s “Hot Spring” in the municipality of Bobonaro, Timor-Leste. In this case, tourism sector in the Bobonaro Municipality has sufficient potential to be developed and it is a tourism sector. The torurism contributes to the increase income of the area and signifies by the movement growth of the economic in Marobo district.. The purpose of the research are (1) to fine the potensial attraction of the natural tourism of “hot spring” Marobo, municipality of Bobonaro, Timor-Leste. (2) To discover the economic impact of the natural attarction “hot spring”development in Marobo, municipality of Bobonaro, Timor-Leste. In this research used both quantitative and qualitative data collecting by observation, documentatios, and interview. The result of the research has show that Marobo Hot spring has natural, cultural and man-made supply potential as tourism attraction. However, the development of Marobo hot spring give economic impact such as, increasing local income, employed opportunities, impact on development and government revenue. Some suggestion will be given for tourist. They should keep the environtment in Marobo Hot spring. Also they have to follow the local regulation in Marobo Hot Spring. The government should offer the good facilities for tourist that can fulfil their need when visited Marobo Hot Spring. Keywords : economic impact, development, tourist attraction, hot spring